1988
DOI: 10.1084/jem.167.6.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human erythrocyte blood group antigens on decay- accelerating factor (DAF) and an erythrocyte phenotype negative for daf

Abstract: Decay accelerating factor (DAF) is a glycoprotein present on the surfaces of many types ofcells in contact with plasma, including erythrocytes, leukocytes, and platelets (reviewed in reference 1). A small amount ofDAF is also present in serum. Numerous investigators have demonstrated that DAF inhibits the action of C3 convertases on cell surfaces, and its absence has been shown to be at least partially responsible for the abnormal sensitivity to lysis by complement exhibited by erythrocytes of patients with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 17 publications
0
70
0
Order By: Relevance
“…33 The cause of hemolysis in this patient is unclear because deficiency of DAF alone does not cause hemolysis. [37][38][39] This suggests that in this C9-deficient PNH patient, as in the mice described here, an increased complement-independent clearance occurs that shortens the half-life of PNH RBCs. The characterization and understanding of this pathway will enable us to delineate its possible clinical importance and possibly determine whether it might also play a role in other diseases with increased RBC clearance.…”
Section: Discussionmentioning
confidence: 96%
“…33 The cause of hemolysis in this patient is unclear because deficiency of DAF alone does not cause hemolysis. [37][38][39] This suggests that in this C9-deficient PNH patient, as in the mice described here, an increased complement-independent clearance occurs that shortens the half-life of PNH RBCs. The characterization and understanding of this pathway will enable us to delineate its possible clinical importance and possibly determine whether it might also play a role in other diseases with increased RBC clearance.…”
Section: Discussionmentioning
confidence: 96%
“…Several polymorphisms have been identified in the noncoding regions ofthe DAF gene by restriction fragment length polymorphisms (RFLP) analysis (3,27). Recently the Cromer blood group antigens (reviewed in 28) have been shown to reside on the DAF molecule (29), so that the serologically identified Cromer blood group alleles mark polymorphisms in the encoded DAF protein. These Cromer blood group phenotypes thus provide a basis for biochemical and functional investigation of alternate forms of DAF.…”
Section: Introductionmentioning
confidence: 99%
“…These individuals differ from PNH patients in that they lack DAF expression in all their tissues, whereas DAF deficiency in PNH patients, resulting from somatic mutations of a gene critical to GPI-anchor biosynthesis (21), is limited to affected blood cells and occurs in conjunction with CD59 dysfunction (12). Furthermore, although DAF gene mutation apparently did not lead to PNH-like disease, two of the five individuals had an intestinal inflammatory disorder (19,20). However, due to the rare nature of DAF gene mutation in the human population, it has not been possible to determine whether such individuals are more susceptible to complement-mediated inflammatory tissue damage.…”
mentioning
confidence: 99%
“…Although in vitro studies have demonstrated that DAF expressed on these cells is functional as a C3 convertase inhibitor (17,18), thus far little direct evidence is available to corroborate the expectation that DAF plays a protective role in vivo on nonvascular cells from complement-mediated injury. In humans, rare cases of complete DAF deficiency due to germline mutation of the DAF gene (Inab serological phenotype) have been identified (19,20). These individuals differ from PNH patients in that they lack DAF expression in all their tissues, whereas DAF deficiency in PNH patients, resulting from somatic mutations of a gene critical to GPI-anchor biosynthesis (21), is limited to affected blood cells and occurs in conjunction with CD59 dysfunction (12).…”
mentioning
confidence: 99%